A Study of Strategic Planning of MICE Tourism in Khon Kaen based on SWOT Analysis - Jiang, Hong; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
The Division of Meeting, Incentive, Conference and Exhibition (MICE) is increasing around the world, especially in Khon Kaen. It is featured as the high consumption, high profit, little seasonal difference and strong industry relevance, so it plays an increasingly important role in the economic development. The city could hold the MICE tourism to improve the visibility and reputation effectively and there is a large room for revenue growth from the business, exhibition, incentive tourism of the foreign visitors and local large-scale team building in Thailand. The local area and region are investigated for the impact of Khon Kaen on the MICE tourism. Most tourists are concentrated in urban areas and such tourism is mainly applied to the exhibition groups, enterprise groups and institutions. However, the local MICE convention and exhibition faces the opportunity and challenge, so the sufficient preparation shall be carried out. In this paper, the authors take the MICE tourism of Khon Kaen as the research objective and the SWOT is selected to judge the management of the local MICE tourism for analysis. The authors will define the development trend and scale based on the basic characteristics of the strategic planning, and detemine the area to be studied, to highlight the strength of MICE